(untitled) (Archaeologia Adriatica, 2018)
This work offers an iconographical-semantical analysis of two large bronze pectorals in the Liburnian culture, from Nin and Zaton (grave 6), symbolically based on the myth of the Sun’s journey through a composition of two “bird boats”, daily and nightly/underground, and iconography of incised scenes, and particularly through a “story” on the disk of the Sun (Nin), in style of “abstract narration”. Mythical story develops through three vertically hierarchized horizontal spheres of the World: heaven-earth-underworld (?). The essence of the myth is depicted in the upper sphere with a complex symbol of “cross in a circle/disk with four dots” (Nin). The symbol denotes that the world is a whole arranged in a cross-shaped manner by the Sun in sign of the number four, divided into four chronological and spatial segments: with fourfold rhythm of time and distribution in four directions/sections. Since “cross in a circle with four dots” is the central code of the solar cult in terms of religion during the (Late) Bronze and Early Iron Age, it is analyzed comparatively, in the communities from the European North to the South. In this work pectorals from Nin and Zaton were defined as the Picenian cultural elements but strongly integrated in the Liburnian culture since the Liburnians and Picenians used solar signs and symbols for a long time in shaping “female” and “male” (funerary) attire.